2020
DOI: 10.1038/s41467-020-16746-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient lensing from a photoemitted electron gas imaged by ultrafast electron microscopy

Abstract: Understanding and controlling ultrafast charge carrier dynamics is of fundamental importance in diverse fields of (quantum) science and technology. Here, we create a three-dimensional hot electron gas through two-photon photoemission from a copper surface in vacuum. We employ an ultrafast electron microscope to record movies of the subsequent electron dynamics on the picosecond-nanosecond time scale. After a prompt Coulomb explosion, the subsequent dynamics is characterized by a rapid oblate-to-prolate shape t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…4(e) . We note that recently Zandi et al 11 reported a very similar periodic lensing effect, using a much smaller beam size (22 μ m in FWHM), where the cyclotron motion will go far beyond the initial plasma size, and is expected to be a pure electron cyclotron oscillation. Indeed, they observed a long-lived (>2 ns) oscillation without frequency evolution.…”
Section: Results and Analysissupporting
confidence: 56%
“…4(e) . We note that recently Zandi et al 11 reported a very similar periodic lensing effect, using a much smaller beam size (22 μ m in FWHM), where the cyclotron motion will go far beyond the initial plasma size, and is expected to be a pure electron cyclotron oscillation. Indeed, they observed a long-lived (>2 ns) oscillation without frequency evolution.…”
Section: Results and Analysissupporting
confidence: 56%
“…Ultrafast electron microscopy (UEM), a technique that integrates fs temporal resolution from ultrafast lasers and atomic spatial resolution from electron microscopies, was established and developed by Zewail and co-workers at Caltech and implemented in transmission ultrafast electron microscopy (T-UEM) in 2006. , T-UEM is a powerful technique for tracking fundamental photoinduced physicochemical events, such as ultrafast phase transformation, anisotropic morphological dynamics, nanoparticle rotational dynamics, phonon dynamics, and many other ultrafast photoinduced dynamic events. Though T-UEM is extremely versatile in many aspects, it is not adequate for mapping the charge carrier dynamics of a material that mostly occurs near the surface and interfaces at a surface-selective manner because of its intrinsic characteristics of a high acceleration voltage (AV) that passes through the specimen and the transmission detection configuration. Therefore, the first generation of scanning ultrafast electron microscopy (S-UEM) was built and developed in 2010 by Zewail and co-workers. , Five years later, Mohammed and co-workers established the second generation of S-UEM in KAUST with better spatial and temporal resolutions. , Since then, S-UEM has demonstrated its superior capability for direct visualization of ultrafast dynamic events that occur near material surfaces and interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The structural and electronic changes in the material are initiated by fs laser pulses, which are followed by similarly short photoelectron pulses for probing the dynamics by means of imaging, diffraction, or electron spectroscopy. In this talk I will present our dynamic environmental TEM setup at UIUC, and I will demonstrate its first application in the field of "plasma lensing" [1]. In our experiment, we generated a hot three-dimensional electron gas by two-photon emission from a copper surface in vacuum.…”
mentioning
confidence: 99%